2019
DOI: 10.1177/0047287519844832
|View full text |Cite
|
Sign up to set email alerts
|

How Far Is the Ideal Destination? Distance Desire, Ways to Explore the Antinomy of Distance Effects in Tourist Destination Choice

Abstract: This study aims to explore the antinomy of distance effects in tourist destination choice by demonstrating its catalytic effect and functionary mechanism. The concept of “distance desire” is proposed to express the catalytic effect of distance, while the attributes and subdivisional dimensions of this concept are also analyzed. A tourist destination decision model is constructed to explore the relationships between the related behavior variables and tourist travel intention. The results of this study indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 70 publications
3
37
0
1
Order By: Relevance
“…Matching may be constrained by: distance in time or space; legal, cultural, or political barriers; or unequal size or power [7]. All these complexities can apply for assortative matching of tourists and destinations [23][24][25].…”
Section: Complexitiesmentioning
confidence: 99%
“…Matching may be constrained by: distance in time or space; legal, cultural, or political barriers; or unequal size or power [7]. All these complexities can apply for assortative matching of tourists and destinations [23][24][25].…”
Section: Complexitiesmentioning
confidence: 99%
“…DIS is the flight distance from the capitals of the origin and destination countries. Distance is a vital variable in people's intention to travel (Cao et al 2019 ), identified as fundamental friction by the gravity model of international trade (Anderson 1979 ). The argument is that the higher the distance between the visitors' home country and intended destination country for leisure travel, the higher the cost of travel, translating into fewer visitors.…”
Section: The Framework Of Analysismentioning
confidence: 99%
“…This research is believed to make important contributions to eliminating the theoretical framework and application-based result deficiency in the related literature in terms of the subject and scale of it. Because the PBT-DD model, which was expanded by associating the DD dimension to the PBT model, was previously tested only in the study of Cao et al (2019).…”
Section: Aim and Scope Of The Researchmentioning
confidence: 99%
“…On the other hand, they try to get as far away as possible and go away (psychological distance) from their usual lives, places, routines, etc. (Cao et al, 2019).…”
Section: Extensive Summary Introductionmentioning
confidence: 99%
See 1 more Smart Citation